Cardiac endothelium: More than just a barrier - Strijdom, Hans; Lochner, Amanda (SA Heart Journal, 2017)
Cardiac endothelium consists of highly specialised endothelial cells that are custom-designed to influence and regulate myocardial function. Various bioactive molecules, such as nitric oxide (NO) are released and given the short diffusion distance between especially the myocardial capillary endothelial cells (cardiac microvascular endothelial cells, CMECs) and adjacent cardiomyocytes, an ideal microenvironment is created for paracrine communication. In this review paper, the relative role of the CMECs with regard to NO generation, the mechanisms of NO generation, and possible consequences of the released NO are described. Particular attention is given to these parameters under conditions of oxygen deficiency, as this is one of the most common pathophysiological conditions affecting the heart.